1998
DOI: 10.1007/s004260050017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and facilitatory effects of cue onset and offset

Abstract: The response speed to a visual target is modulated by the position of previous events (cues) even if their position is not predictive of the target position. The modulation has been considered biphasic, with an early facilitatory and a later inhibitory component. We conducted three experiments that investigated the importance of the onset and oset features of the cue for the facilitatory and inhibitory eects and estimated their separate and joint eects. The two possible target locations, one in the right and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
45
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 42 publications
9
45
4
Order By: Relevance
“…Further differences between stimulus onsets and offsets in a spatial cuing task were obtained by Pratt and Hirshhorn (2003). These authors demonstrated that offset cues produced considerably earlier effects of inhibition of return (IOR) than did onset cues (see also Gawryszewski, Thomaz, Machado-Pinheiro, & Sant'Anna, 1994;Riggio, Bello, & Umiltà, 1998;and Samuel & Weiner, 2001, for further results of onset-offset investigations in spatial cuing). Hopfinger and Maxwell (2005) conducted an electrophysiological study investigating bottom-up, sensory-driven effects of onset and offset stimuli on subsequent stimulus processing.…”
Section: Apparatus and Stimulimentioning
confidence: 92%
“…Further differences between stimulus onsets and offsets in a spatial cuing task were obtained by Pratt and Hirshhorn (2003). These authors demonstrated that offset cues produced considerably earlier effects of inhibition of return (IOR) than did onset cues (see also Gawryszewski, Thomaz, Machado-Pinheiro, & Sant'Anna, 1994;Riggio, Bello, & Umiltà, 1998;and Samuel & Weiner, 2001, for further results of onset-offset investigations in spatial cuing). Hopfinger and Maxwell (2005) conducted an electrophysiological study investigating bottom-up, sensory-driven effects of onset and offset stimuli on subsequent stimulus processing.…”
Section: Apparatus and Stimulimentioning
confidence: 92%
“…Almost all single-response IOR experiments have used target-absent trials as catch trials (Donder's a-task, used by Maylor & Hockey, 1985;Posner & Cohen, 1984;Possamaï, 1986Possamaï, , 1991Reuter-Lorenz et al, 1996;Riggio, Bello, & Umiltà, 1998). A disadvantage of this task (Sperling & Dosher, 1986) is that FAs cannot be attributed to a cued trial or an uncued trial.…”
Section: The Effects Of Inhibition Of Returnmentioning
confidence: 99%
“…A variety of experimental variables have been shown to affect the presence, onset latency, and magnitude of IOR. Some of these factors are response task (see, e.g., Lupiáñez, Milán, Tornay, Madrid, & Tudela, 1997), target intensity (see, e.g., Reuter-Lorenz, Jha, & Rosenquist, 1996), target modality (Reuter-Lorenz et al, 1996), and the type of cue used (Riggio, Bello, & Umiltà, 1998). However, relatively few studies have systematically examined how these variables interact.…”
mentioning
confidence: 99%